Evaluation of skin absorption of drugs from topical and transdermal formulations (Brazilian Journal of Pharmaceutical Sciences, 2016)
The skin barrier function has been attributed to the stratum corneum and represents a major challenge in clinical practice pertaining to cutaneous administration of drugs. Despite this, a large number of bioactive compounds have been successfully administered via cutaneous administration because of advances in the design of topical and transdermal formulations. In vitro and in vivo evaluations of these novel drug delivery systems are necessary to characterize their quality and efficacy. This review covers the most well-known methods for assessing the cutaneous absorption of drugs as an auxiliary tool for pharmaceutical formulation scientists in the design of drug delivery systems. In vitro methods as skin permeation assays using Franz-type diffusion cells, cutaneous retention and tape-stripping methods to study the cutaneous penetration of drugs, and in vivo evaluations as pre-clinical pharmacokinetic studies in animal models are discussed. Alternative approaches to cutaneous microdialysis are also covered. Recent advances in research on skin absorption of drugs and the effect of skin absorption enhancers, as investigated using confocal laser scanning microscopy, Raman confocal microscopy, and attenuated total reflectance Fourier-transform infrared spectroscopy, are reviewed.